RESILIENCE: PROTECTIVE FACTOR AND OUTCOME (LITERATURE REVIEW) - Wiwik Triwidiyanti (PT. Antis International Publisher, 2026)
Objective: Resilience is an individual's ability to maintain adaptive functioning and recover optimally after facing stress, difficulties, or psychosocial risk experiences. The study aims to explore the dynamic nature of resilience and identify the factors influencing it. Method: The research method used is a literature review, with the literature for this study accessed by the author from electronic document providers such as Google Scholar, Scopus, EBSCO, and Science Direct. The researcher searched for literature using the keywords